Aromaterapi Minyak Esensial Bergamot Menurunkan Resiko Postpartum Blues - Inke Malahayati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The new role as a mother begins after delivery, especially in primigravidas. Psychological disorders can hinder the achievement of motherhood. The incidence of postpartum blues ranges from 40-85%. Postpartum blues is often not realized so that it can lead to postpartum depression. Various attempts have been made to overcome the postpartum blues including aromatherapy. The purpose of this study was to determine the effect of giving bergamot essential oil aromatherapy on postpartum blues. This type of study was quasi-experimental with a pretest and postest one group design. The study was conducted on 20 post-cesarean mothers aged 15-49 years, parity 1-5, term pregnancy, babies born with an Apgar score of 7-10, no history of asthma, allergies, or dermatitis to flowers/plants, able to read and write well in Indonesian, and an EPDS score of 10-12 (between the third to the fifth day). Sampling was consecutive sampling. EPDS score measurements were performed three times (baseline, 7th day, and 14th day). Data analysis used the Shapiro Wilk, Friedman, and posthoc Wilcoxon tests with α = 0.05 and β = 80%. The mean age of the respondents was 30.30 ± 6.24, multiparous 55%, SMA 70%, housewives 11%. The mean EPDS scores at baseline, day 7, and day 14 were 11.35 ± 0.81, respectively; 8.00 ± 3.09; and 5.45 ± 3.50 (p